THE EFFECT OF MORINGA (Moringa oleifera) LEAF EXTRACT GIVEN INTO DRINKING WATER ON EGG PRODUCTION OF LOHMANN BROWN CHICKEN AGED 22-30 WEEKS - I M. D., Luki Ananta; Suasta, I M.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
This research was conducted to determine the effect of moringa ( Moringa oleifera ) leaves extract given into drinking water to egg production of Lohmann Brown chicken aged 22-30 weeks.  The research was conducted in Dajan Peken Village, Tabanan for three months, has begun in January to March.  The design used was Completely Randomized Design (CRD) with three treatments and six replications.  The treatments are 0% of Moringa ( Moringa oleifera ) leaves extract given into drinking water as control (K0), 3% (K1), and 6% (K2).  The research used 36 Lohmann Brown chicken with homogeneous conditioned.  Variables obserbed were feed consumption, water consumption, feed coversion ratio (FCR), hen day production (HDP), egg production, total egg weight, and average egg weight.  The results showed that the addition Moringa ( Moringa oleifera ) leaves extract into drinking water at level 3% and 6% was significant (P<0,05) increase feed and drinking water consumption, egg total, hen day production (HDP), total egg weight and average egg weight but lowering feed conversion ratio (FCR) of Lohmann Brown chicken aged 22-30 weeks.  The conclusion of this research is giving moringa ( Moringa oleifera ) leaves extract at level 3% and 6% into drinking water can increase egg productions of Lohmann Brown chicken aged 22-30 weeks. Keywords     :  Lohman Brown chicken, Moringa (Moringa oleifera) leaves, Egg productions